Global reform of personal income taxation, 1981 - 2005: evidence from 189 countries - Klara Sabirianova Peter; Steve Buttrick; Denvil Duncan (Institute for the Study of Labor (IZA), 2009)
In this paper we use a panel of 189 countries to describe the salient trends that have emerged in national personal income tax systems spanning the twenty five year period from 1981 to 2005. Using complete national income tax schedules, we calculate actual average and marginal tax rates at different income levels as well as time-varying measures of structural progressivity and complexity of national tax systems. We show that frequent alterations of tax structures have reduced tax rates at higher levels of income and diminished the overall progressivity and complexity of national tax systems; however, the degree of this change varies considerably across countries. We also find that the relationship between the tax rates and revenue is positive for high income countries; however, the strength of the relationship declines with weaker institutions and lower levels of economic development.
urn:nbn:de:101:1-2009062295
Keywords: C8; E62; H2; H87; N10; O1; 330; Personal income tax; marginal rate; average rate; tax complexity; progressivity; flat tax; revenue; global trends; Einkommensteuer; Steuerreform; Steuerprogression; Steuerbelastung; Steuervereinfachung; Flat Tax; Vergleich; Welt